Apoyo como pasante en ejecución de proyectos civiles en el Consorcio GCIPA, Duitama Boyacá (2024)
This document is presented in the internship modality as a degree requirement to obtain the title of Civil Engineer from the Antonio Nariño University, which aims to carry out the practice in the GCIPA consortium of the Municipality of Duitama-Boyacá supporting the control and work monitoring by calculating the quantity of materials, work supervision, writing monthly reports, preparing plans in AutoCAD software and designing a work log which was left at the disposal of the consortium.